Anteseden dari Green Buying Behaviour - Dika Septariana; Luki Adiati Pratomo (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2020)
The aim of this study is to examine the factors that can influence green buying behavior. Factors to be investigated are personal norm, social environmental norm, peer influence, and green self-identity. The research design used in this study is hypothesis testing with a purposive sampling technique. The number of respondents is 200, with the specific criteria is consumers who understand and consume environmentally friendly products in the past year. The results showed that the four variables, namely personal norm, social environmental norm, peer influence, green self-identity, had a positive influence on green buying behavior.